Incidence of Oculocardiac Reflex in Pediatric Population Undergoing Corrective Strabismus Surgery: Comparison between Sevoflurane and Total Intravenous Anesthesia - Roodneshin, Fatemeh; Poor Zamany Nejat Kermany, Mahtab; Rostami, Pooya; Niksan, Omid (Novelty in Biomedicine, 2018)
Background: Oculocardiac reflex (OCR) is a life threatening, possible complication of corrective strabismus surgery and is more common among the pediatric patients. Sevoflurane and Propofol are the most commonly used agents in pediatric surgery. This study aimed to compare the effect of these two agents on oculocardiac reflex during corrective strabismus surgery in pediatrics patients. Materials and Methods: A total of 89 children were divided in two groups and no significant demographic data difference was between the two groups. Group 1 (n=45) received sevoflurane 6-8% as induction agent followed by 2-3% for maintenance, group 2 (n=44) was injected with propofol 3mg/kg as induction agent followed by 200µg/kg/min infusion as the maintenance dose, bispectral index (BIS) was kept 40-60 in both groups. Oculocardiac reflex was compared between the two groups. Results: Incidence of OCR of group 1was showed a significant decrease. Conclusion: Sevoflurane reduced the incidence of OCR. Sevoflurane may be the agent of choice in corrective strabismus surgery, compared to propofol.